Humeral epicondylitis among gas- and waterworks employees - Ritz, B. R. (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'In this cross-sectional study 290 male employees of the public gas- and waterworks of Hamburg, Germany, were examined for symptoms of epicondylitis. Forty-one workers were diagnosed with symptoms of lateral or medial epicondylitis. The effect of employment in different job categories on the prevalence of epicondylitis was explored.' ' METHODS ': 'The diagnosis of epicondylitis was based on the study's own criteria and compared with criteria used in former studies. Jobs were categorized into high, moderate, and no exposure groups according to tasks regarded as strenuous for the elbow. The data were analyzed with the help of multivariate logistic regression.' ' RESULTS ': 'With the study's diagnostic criteria, the prevalence odds ratio (OR) for 10 years of high exposure to elbow straining work was 1.7 [95% confidence interval (95% CI) 1.04–2.68] for currently held jobs and 2.16 (95% CI 1.08–4.32) for formerly held jobs. For workers regarded as moderately exposed in current jobs the odds ratio for 10 years was 1.4 (95% CI 1.00–1.93). Very similar results were obtained for current exposure when stricter diagnostic criteria were employed.' ' CONCLUSION ': 'The results suggest a cumulative exposure effect with length of employment. Workers with high exposure in former jobs compared with employees with high exposure in their current job exhibited more residual or slight epicondylitis symptoms upon examination.
Keywords: cumulative exposure; job history; mechanics; MSD; multivariate analysis; musculoskeletal disorder; pipefitter; welder; work-related factor